THE INFLUENCE OF GOVERNMENT POLICIES IN THE RELATIONSHIPS SUPPLY CHAIN ON COMPANY PERFORMANCE IN IMPROVING MICRO AND MACRO ECONOMICS - Indira Santi Kertabudi (Universal Journal, 2022)
The purpose of this study is to explain the effect of supply chain integration on company performance mediated by government policies in strengthening macro and micro economies. The approach used in this research is the quantitative method. Where is the population of 5 nickel mining companies in Sulawesi, represented by 500 employees. From the total population, samples were then taken using the Slovin formula with a margin of error of 5 percent totaling 222 employees. Of these, 200 questionnaires returned with valid conditions. Smart PLS 3 was used to analyze the research data. The results of the research show that the supply chain has a significant effect on the company's performance. Improved company performance strengthened by government policies so as to increase the company's profitability significantly .